Design and Development of Smart Irrigation System for Watering Rooftop Garden - Zaman , Rokon Uz (Review of Plant Studies, 2022)
Rooftop gardening is one of the famous agricultural technology in urban areas of many countries including Bangladesh. Crop water requirement is very high in rooftop due to high temperature and high evapotranspiration. Irrigation as well as water management is the major limitation for this practice. Considering the necessity of rooftop gardening in urban areas and irrigation issue, it is essential to develop a low cost efficient irrigation method that helps to improve production techniques for rooftop garden. From this study, we developed a smart irrigation system for watering rooftop gardening where mainly used programmable digital timer, solenoid valve and electric pump operated drip system. In this irrigation system, programmable digital timer sends a signal to the solenoid valve and electric pump that leads to open or close the whole irrigation system and crop was watered the selected interval and frequency wise. From the results, average discharge (Qavg), distribution efficiency (Ed), application efficiency (Ea), coefficient of variation for emitter flow (cv) and statistical uniformity coefficient (SUC) were achieved good performance and was found meeting American Society of Agricultural Engineers (ASAE) standards. The designed smart irrigation system was operated excellently as the values of emission uniformity.